Wnt/β-catenin Signaling Inhibitors - Zhang, Xun; Dong, Nazhen; Hu, Xiaoyan (Current Topics in Medicinal Chemistry, 2023)
The Wnt/β-catenin signaling pathway plays a crucial role in the development, tissue homeostasis, angiogenesis, and carcinogenesis of cancer. Mutations and excessive activation of the Wnt/β-catenin signaling pathway in cancer cells and cancer stem cells lead to drug resistance and recurrence of cancer in patients treated with conventional chemotherapy and radiotherapy. Upregulation of proangiogenic factors is persistently induced by hyperactivated Wnt/β-catenin signaling during tumor angiogenesis. Furthermore, mutations and hyperactivated Wnt/β-catenin signaling are associated with worse outcomes in several human cancers, including breast cancer, cervical cancer, and glioma. Therefore, mutations and hyperactivation of Wnt/β-catenin signaling create challenges and limitations in cancer treatment. Recently, in silico drug design as well as high-throughput assays and experiments have demonstrated the promising anticancer efficacy of chemotherapeutics, such as blocking the cancer cell cycle, inhibiting cancer cell proliferation and endothelial cell angiogenesis, inducing cancer cell apoptosis, removing cancer stem cells, and enhancing immune responses. Compared to conventional chemotherapy and radiotherapy, small-molecule inhibitors are considered the most promising therapeutic strategy for targeting the Wnt/β-catenin signaling pathway. Herein, we review the current small-molecule inhibitors of the Wnt/β-catenin signaling pathway, focusing on Wnt ligands, Wnt receptors, the β-catenin destruction complex, ubiquitin ligases and proteasomal destruction complex, β-catenin, β-catenin-associated transcriptional factors and coactivators, and proangiogenic factors. We describe the structure, mechanisms, and functions of these small molecules during cancer treatment in preclinical and clinical trials. We also review several Wnt/β-catenin inhibitors reported to exhibit anti-angiogenic effects. Finally, we explain various challenges in the targeting of the Wnt/β-catenin signaling pathway in human cancer treatment and suggest potential therapeutic approaches to human cancer.
Keywords: Angiogenesis